Optimasi Peningkatan Self-Control melalui Teknik Self-Hypnosis - Wayan Eka Paramartha; I Ketut Dharsana; Kadek Suranata (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
The improvement of self-control is a key factor in enhancing academic achievement and the quality of students' lives. Therefore, this research aims to explore strategies for enhancing self-control through the application of self-hypnosis techniques among students. The research employed a random sampling technique by randomly selecting classes as samples. The total number of participants involved in this study was 60 individuals. Statistical analysis was conducted using the ANCOVA method. The results of the study revealed that the application of self-hypnosis techniques significantly increased the level of self-control among students. It was found that the experimental group, which received the self-hypnosis technique, experienced a significant improvement in self-control compared to the control group. This finding remained significant even after controlling for initial variables that may have influenced the results, such as the participants' initial level of self-control before the intervention.The findings indicate that self-hypnosis techniques can be an effective strategy for enhancing self-control among students. By utilizing these techniques, students can develop the ability to regulate themselves, manage their emotions, and overcome distractions that may hinder their academic performance and daily lives. The implications of this study highlight the importance of introducing self-hypnosis techniques as part of personal development programs for students.